Botulinum toxin type A and acupuncture for masticatory myofascial pain: a randomized clinical trial - De La Torre Canales, Giancarlo; Câmara-Souza, Mariana Barbosa; Poluha, Rodrigo Lorenzi; Grillo, Cassia Maria; Conti, Paulo César Rodrigues; Souza, Maria da Luz Rosário de; Rodrigues Garcia, Renata Cunha Matheus; Rizzatti-Barbosa, Célia Marisa (Journal of Applied Oral Science, 2021)
BoNT-A has been widely used for TMD therapy. However, the potential benefits compared to dry needling techniques are not clear. Objective: this study aimed to compare the immediate effects of botulinum toxin type A (BoNT-A) injections and Acupuncture in myofascial temporomandibular disorders (TMD) patients. Methodology: 54 women were divided into three groups (n=18). AC patients received four sessions of traditional acupuncture, being one session/week during 20-min. BoNT-A patients were bilaterally injected with 30U and 10U in masseter and anterior temporal muscles, respectively. Moreover, a control group received saline solution (SS) in the same muscles. Self-perceived pain was assessed by visual analog scale, while pressure pain threshold (PPT) was verified by a digital algometer. Electromyographic evaluations (EMG) of anterior temporal and masseter muscles were also measured. All variables were assessed before and 1-month after therapies. The mixed-design two-way repeated measures ANOVA and Tukey’s post-hoc tests were used for analysis, considering a=0.05. Results: Self-perceived pain decreased in all groups after one month of therapy (P<.001). BoNT-A was not better than AC in pain reduction (P=0.05), but both therapies were more effective in reducing pain than SS (P<0.05). BoNT-A was the only treatment able to improve PPT values (P<0.05); however, a severe decrease of EMG activity was also found in this group, which is considered an adverse effect. Conclusion: after one month of follow-up, all therapies reduced the self-perceived pain in myofascial TMD patients, but only BoNT-A enhanced PPT yet decreased EMG.